(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Man is a self-conscious being, endowed with reason and subject to the status of personality. The status of personality is the status of human freedom and regulates three fundamental principles of universal freedom: freedom, authenticity and responsibility. No one may choose or reject in the place of the person concerned. Not even the Divinity. Every man must be of his own choosing. – Authenticity is the concrete inalienable quality of rejecting or actually accepting, rightly, an action or an idea that is the product of one’s own will. Each action or non-action must be its own. Every man must be, in his action, himself. – Responsibility is the inevitable quality of any person to answer, rightly, of their own choice and authenticity. The quality of being free and the quality of being authentic are not random. Every action of a person has repercussions on God and on his neighbor. Because of this, everyone is responsible for himself.